Blondel and the crisis of modernism - Boey, Koen (International journal of philosophy and theology, 2018)
When Maurice Blondel raised the problem of Christian salvation in his thesis L'Action', he met with heavy resistance, both from the French University, striving for rationality and from the traditional Catholic philosophers who rejected the modern' method of immanence. Whereas in the sphere of knowledge Hegel starts the search for Absolute Knowledge from the uncultivated consciousness on, Blondel, exploring the sphere of the will, goes out from the most primitive willing of something' so as to climb - equally dialectically - towards the object of the ultimate desire of the will. To Blondel, this path presupposes overcoming the position of positivism. Blondel reckons only with the ethical drive of the will's desire. The way he chooses allows him to penetrate as far as to the natural desire of god, fulfilled by revelation. The act of faith, however, does not belong to philosophy. The fierce discussions after the publication gave Blondel the opportunity to expound his idea of a Christian philosophy. It is apologetics indeed, seen from the intention of the philosopher. But the philosophical work he performs must fully comply with the philosophical profession and rest upon rational arguing only. His work, meant as une science de la vie et une critique de la pratique'', is his attempt to meet these standards.